1993
DOI: 10.1093/ajcn/57.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Severe vs moderate energy restriction with and without exercise in the treatment of obesity: efficiency of weight loss

Abstract: Thirty obese women were randomly assigned to either 40% [severe energy restriction (SER)] or 70% [moderate energy restriction (MER)] of their maintenance energy requirements and to no exercise, aerobic exercise (walking), or aerobic exercise plus circuit weight training. Body composition by hydrostatic weighing and energy expenditure by indirect calorimetry were measured at 0, 3, and 6 mo. In addition, we developed a deficit-efficiency factor (DEF), calculated as body energy loss/dietary energy deficit, to att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 22 publications
3
38
0
5
Order By: Relevance
“…90,93 Theoretically, a similar rationale for preserving fat-free mass would apply when selecting an optimal treatment for overweight in youth.…”
Section: Discussionmentioning
confidence: 99%
“…90,93 Theoretically, a similar rationale for preserving fat-free mass would apply when selecting an optimal treatment for overweight in youth.…”
Section: Discussionmentioning
confidence: 99%
“…40 Besides these considerations, the use of this type of diet seems to promote, in the course of time, adaptation mechanisms that allow the body greater conservation of energy, making it necessary to decrease the energy ingestion in order to maintain weight. 41 On the other hand, Amador et al 42 demonstrated that growing children can substantially improve their body composition without actual weight loss, with the use of the normocaloric diet associated with physical activity. In the present study, both groups of girls and boys gained weight from the beginning of treatment, but the majority were able to reduce their body size.…”
Section: Discussionmentioning
confidence: 99%
“…(76) A moderately energy-restricted diet (MER) was defined as a diet providing greater or equal to 5.0 MJ per day. (78) BMD in all studies was reported as grams per square centimeter (g/cm 2 ). Data for lumbar spine BMD measured between L 1 and L 4 were pooled with data measured between L 2 and L 4 .…”
Section: Methodsmentioning
confidence: 99%